The impact of exercise on growth factors in postmenopausal women: a systematic review and meta-analysis - Yasaman Nasir; Mohammad Reza Hoseinipouya; Hesam Eshaghi; Mohammad Hossein Rahimi (BMC, 2024)
Abstract Background Aging results in many changes in health status, body composition, muscle strength, and, ultimately, functional capacity. These changes coincide with significant alterations in the endocrine system, such as insulin-like growth factor-1 (IGF-1) and IGF-binding proteins (IGFBPs), and may be associated with many symptoms of aging. The objectives of this study is to investigate the potential influence of different types of exercise, such as resistance training and aerobic training, on IGF-1 and IGFBP-3 levels in postmenopausal women. Methods Medline, Scopus, and Google Scholar databases were systematically searched up to November 2023. The Cochrane Collaboration tool was used to assess the risk of bias and the quality of the studies. The random-effects model, weighted mean difference (WMD), and 95% confidence interval (CI) were used to estimate the overall effect. Between-study heterogeneity was assessed using the chi-squared and I2 tests. Results Seventeen studies were included in the present systematic review and 16 studies were included in the meta-analysis. The pooled results from 16 studies (21 trials) with 1170 participants examining the impact of exercise on IGF-1 concentration showed a significant increase in IGF-1, and the pooled results among six studies (trials) showed a significant decrease in IGFBP-3 concentration (730 participants). In addition, resistance training and aerobic training had a significant effect on increasing IGF-1 concentration post-exercise compared with placebo. Conclusion Based on this meta-analysis, Women who have completed menopause and followed an exercise routine showed changes in IGF-1 and IGFBP-3 levels that can indirectly be associated with risk of chronic age-related conditions.